2011
DOI: 10.1111/j.1369-1600.2011.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin and topiramate regulate behavioural and brain gene transcription changes induced by spontaneous cannabinoid withdrawal in mice

Abstract: This study examined the actions of pregabalin and topiramate on behavioural and gene transcription alterations induced by spontaneous cannabinoid withdrawal in mice. Tolerance was induced in mice by administration of CP-55,940 (0.5 mg/kg/12 hours; i.p.; 7 days). Behavioural assessment of spontaneous cannabinoid withdrawal was performed by measuring motor activity, somatic signs and anxiety-like behaviour on days 1 and 3 after cessation of treatment with CP-55,940. On days 1-3 of cannabinoid withdrawal, mice re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 51 publications
3
31
0
Order By: Relevance
“…In addition, pregabalin was found to reduce anxiety‐like behavior induced by cannabinoid withdrawal in mice (Aracil‐Fernández et al . ). Of particular relevance to our finding is the evidence that pregabalin was effective in a rat model of post‐traumatic stress disorder induced by a 10‐min exposure to predator urine scent (well‐soiled cat litter for 10 min).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, pregabalin was found to reduce anxiety‐like behavior induced by cannabinoid withdrawal in mice (Aracil‐Fernández et al . ). Of particular relevance to our finding is the evidence that pregabalin was effective in a rat model of post‐traumatic stress disorder induced by a 10‐min exposure to predator urine scent (well‐soiled cat litter for 10 min).…”
Section: Discussionmentioning
confidence: 97%
“…Data shown in Figure 1 clearly indicate that pregabalin presents a potent anxiolytic effect, increasing the time spent in the lighted and open side at all doses tested, supporting the previous hypothesis. Indeed, recent data from a study by our group demonstrated that pregabalin reduces the increase in the anxiety level produced by spontaneous cannabinoid withdrawal in mice (Aracil‐Fernandez et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example the synthetic cannabinoid, WIN55,212–2 induced wet dog shakes and facial rubs in male rats (Aceto et al, 2001). Similarly, repeated CP55,940 administration induces somatic withdrawal signs and increases plasma corticosterone (Oliva et al, 2004, 2003), and also reduces time in the dark side of the light/dark box in male mice (Aracil-Fernández et al, 2011). In adolescent rats exposed to repeated THC, males spent more time in the open arms of the elevated plus maze and females spent more time in the closed arms during abstinence following repeated THC exposure (Harte-Hargrove and Dow-Edwards, 2012).…”
Section: Discussionmentioning
confidence: 99%